Use of NTrap® during Ureteroscopic Lithotripsy for Upper Ureteral Stones - Lee, Moung Jin (The Korean Urological Association, 2010)
PURPOSE: This study aimed to determine the value of the NTrap® (Cook Urological INC, USA), which was designed to block the upward movement of stones during ureteroscopic lithotripsy. MATERIALS AND METHODS: We reviewed the data of 144 patients who underwent ureteroscopic lithotripsy for an upper ureteral stone from June 2006 to May 2010. Sixty-eight patients who underwent ureteroscopic lithotripsy without the use of the NTrap® were assigned to Group I and 76 patients who underwent ureteroscopic lithotripsy with the NTrap® were assigned to Group II. The size of the stones, operation time, success rate, and pre- and postoperative complications were compared retrospectively between the two groups. RESULTS: The mean age of the patients (Group I: 35.8 years; Group II: 32.6 years) and the sex ratios were not significantly different between the two groups. The mean size of the stones was 6.9 mm and 7.4 mm, which also was not significantly different between the two groups. The mean operation time was 82.7 minutes and 78.7 minutes. The operation time was shorter in Group II, but the difference was not significant. The success rate of stone removal was 89.7% and 98.7% in Groups I and II, respectively; Group II showed a significantly higher success rate. Two cases of ureteral perforation and one case of ureteral avulsion occurred in Group I, and one case of ureteral perforation occurred in Group II. CONCLUSIONS: NTrap®, which is an instrument used to assist during ureteroscopic lithotripsy, can be considered to be an effective tool that blocks the upward movement of the stone and aids in safe stone removal.